Utilization of dental health-care services and its barriers among the patients visiting community health centers in Nellore District, Andhra Pradesh: A cross-sectional, questionnaire study - P Nagarjuna; V Chandra Sekhara Reddy; K M Sudhir; R. V. S. Krishna Kumar; Srinivasulu Gomasani (Wolters Kluwer Medknow Publications, 2016)
Introduction: The primary health centers and community health centers (CHCs) offer an opportunity for early diagnosis and treatment, dental health education, and institution of preventive measures in the remote areas. Aim: To assess the level of utilization of dental health care services and to determine barriers that prevent utilization of dental health-care services among the patients visiting CHCs in Nellore District, Andhra Pradesh. Materials and Methods: A cross-sectional study was carried out among 600 patients aged 20 years and above visiting the randomly selected 10 CHCs during May 2015 in Nellore District. A multistage sampling method was followed. The source of data was primary in nature and it was obtained through self-administered questionnaire. Data was entered and analyzed using a software program IBM SPSS Statistics version 22 (Armonk, NY: IBM Corp) (P < 0.05). Results: Only 36% of patients had visited the dentist in the last 12 months. Males (54%) visited dentist more frequently than females (46%). The most common reported reasons for the last dental visit were pain or a dental emergency (71%), followed by restorative treatment (17%) and other reasons (12%). The most commonly reported reasons for not seeking dental care were "Not needed unless having pain" by 360 (60%), "I do not think dental diseases are very serious" by 304 (51%), "I have fear of dental procedures" by 290 (48.6%),"Lack of time" by 235 (45.6%), "Dental treatment is expensive" by 200 (33.3%), and "The dentist is at a long distance" by 158 (26.8%). Conclusions: Our findings suggest that only a small portion of population visited a dentist in previous year. Most of them believe that visiting dentist is necessary only for pain relief.